Micromorphological studies of Anisochilus scaber Benth. - Farsana, S S; Viji, V; Gayatri, G P; Geetha, M D; Hyzil, J B; Jaya, C S K (Plant Science Today, 2026)
The diversity in trichome characters plays a major role in taxonomical and physiological studies. The present study aims to analyze the structural diversity of trichomes in Anisochilus scaber Benth. using scanning electron microscope and bright field microscope. In this species two basic types of trichomes were observed, glandular and non-glandular. The glandular trichomes consist of peltate and capitate types. Non-glandular trichomes were multicellular, simple or branched. These trichomes were recognized in tender leaf, mature leaf, tender stem and sub-mature stem. However, its distribution pattern varies among the plant parts. Trichomes were almost completely absent in mature stem. The stomata identified were diacytic in nature. Difference in stomatal index is observed between tender and mature leaves. Highest percentage of stomatal index is seen in the abaxial surface of the tender leaf.